2021
DOI: 10.1039/d1ra04470b
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of solution processed photodetectors comprised of two-dimensional tin(ii) sulfide nanosheet thin films assembled via the Langmuir–Blodgett method

Abstract: Norton et al. report the manufacture of fully solution processed photodetectors based on two-dimensional tin(ii) sulfide assembled via the Langmuir–Blodgett method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Since the size of nanodot and nanorod was obviously large compared to the exciton Bohr radius, it is expected that the quantum size effect hardly appeared. Considering the indirect bandgap energy of 0.80 eV in bulk SnSe and that of 0.92 eV in bulk SnS, 45,46) the energy values of SnS 0.5 Se 0.5 nanodot and SnS 0.1 Se 0.9 nanorod are quite reasonable. On the other hand, the bandgap energy of SnSe nanosheet was higher than that of SnS 0.1 Se 0.9 nanorod and SnS 0.5 Se 0.5 nanodot.…”
Section: Top-snsse Nanocrystalsmentioning
confidence: 88%
“…Since the size of nanodot and nanorod was obviously large compared to the exciton Bohr radius, it is expected that the quantum size effect hardly appeared. Considering the indirect bandgap energy of 0.80 eV in bulk SnSe and that of 0.92 eV in bulk SnS, 45,46) the energy values of SnS 0.5 Se 0.5 nanodot and SnS 0.1 Se 0.9 nanorod are quite reasonable. On the other hand, the bandgap energy of SnSe nanosheet was higher than that of SnS 0.1 Se 0.9 nanorod and SnS 0.5 Se 0.5 nanodot.…”
Section: Top-snsse Nanocrystalsmentioning
confidence: 88%
“…Fabrication of large-area, ordered, thickness-tunable nanowire materials at the gas-liquid interface with low environmental requirements for preparation, makes the LB method suitable for application in the field of photoelectric detection. 150,151,172,214 As shown in Fig. 11E, Wang et al realized the highly integrated thin film fabrication of KCu 7 S 4 semiconductor nanowires by the LB technique.…”
Section: Optoelectronic Applicationsmentioning
confidence: 99%
“…Kane et al demonstrated a method to assemble LB thin films of SnS 2D nanosheets. 150 Homogeneous films at the gas–liquid interface formed using SnS nanosheets with an average peel thickness of 33 nm with chloroform as the diffusion solvent were deposited onto Si/SiO 2 substrates (94.4% surface coverage), exhibiting excellent photo-response properties. Mao et al constructed large-area homogeneous black phosphorus (BP) nanosheet films by mixing with C 60 , which effectively suppresses the face-to-face stacking phenomenon between BP nanosheets, showing the potential for photovoltaic applications.…”
Section: Functional Materials/structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…42 Single source precursors (SSPs) such as metal xanthate and metal dithiocarbamate complexes are also favourable as they have pre-arranged M-S bonds and therefore enable an atom-up approach towards metal sulfides. 42 SSPs have been demonstrated as a scalable, facile, low-temperature and fast route towards particulate, [43][44][45] thin film, 41,[46][47][48] and nanomaterial [49][50][51][52][53] metal sulfides. It has also been demonstrated that by altering the chemistry of the SSPs and the environment of the decomposition of the precursors, shape, size, and phase control is possible.…”
Section: Introductionmentioning
confidence: 99%